The use of contextual teaching approach and Learning (ctl) to increase power and squared root in Sd negeri 21 kapuh kecamatan koto xi tarusan - Yasrimar Yasrimar (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Based on the observations of researchers on learning outcomes powers and simple roots in class V SD Negeri 21 Kapuh District of Koto XI Tarusan yet still not maximized. This is because the learning process is more often focused on teachers alone. the purpose of this study is to describe and obtain information about the learning powers and simple roots by using CTL approach to improve student learning outcomes that include planning, implementation and learning outcomes. The approach used classroom action research is qualitative and quantitative approaches. A qualitative approach is an approach that produces descriptive data in the form of written words while the quantitative approach is a research approach that emphasizes the numeric data (numbers). This type of research is classroom action research. By using action research design that includes planning, implementation, observation and reflection. This study showed an increase in student learning outcomes in learning powers and simple roots by using CTL approach. It can be seen from the ability of teachers to design lesson plan first cycle of 67.85% and 78.57%. Cycle II 92.85% and 92.85%. Teacher activity cycle I 57.14% and 82.14%, 85.71% and cycle II 92.85%. Student activity cycle I 67.85% and 78.57%. Cycle II 85.71% and 92.85%. The results of students in the first cycle on the cognitive aspects of 66.17 and 70.03, 73.33 and 72.22 affective, psychomotor 73.89 and 73.61. In the second cycle on the cognitive aspects of 80.50 and 85.57, 76.67 and 91.11 affective, psychomotor 83.89 and 91.11. This indicates that the CTL approach can improve student learning outcomes in learning powers and simple roots.